Die soziale Konstruktion von Qualifikation: Eine historische Untersuchung der Weberei von Lancashire zwischen 1885 und dem Ersten Weltkriegh.lech.te:rverhältnis - Schwarzkopd, Jutta (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1993)
The consideration of skill highlights the social construction of job hierarchies. This investigation of the wage-levels as well as the level and distribution of skill in the Lancashire weaving industry between 1885 and the First World War corroborates the largely ideological character of »skill« as a measure for the classification of work. In the social construction of women-dominated weaving as »semiskilled «, the gender-specific dimension is shown to be of overriding importance. This study further suggesrs that the gender hierarchy in society at ]arge determines the relation of warnen and men at the working-place to such an extent as to obviate its being undermined from within the labour process. Yet experiences gained at work appear to carry the potential for warnen to pose a challenge to the existing hierarchy in a different social sphere.